Xist gene regulation at the onset of X inactivation. - Senner, C; Brockdorff, N (2009)
The large non-coding RNA Xist is the master regulator of X inactivation. Xist is negatively regulated by its antisense transcript Tsix. This repressive antisense transcription across Xist operates at least in part through the modification of the chromatin environment of the locus. However Tsix is not sufficient to repress Xist in pluripotent cells and there is emerging evidence that transcription factors associated with pluripotency are involved in Tsix-independent repression. This review focuses on recent advances in this area and discusses the implications for our understanding of Xist gene regulation at the onset of X inactivation.